Ambipolar pentacyclic diamides with interesting electrochemical and optoelectronic properties. Issue 94 (12th November 2020) - Marques, Carolina S.; Cruz, Hugo; Lawrence, Simon E.; Gago, Sandra; Prates Ramalho, João P.; Morgado, Jorge; Branco, Luís C.; Burke, Anthony J.
Abstract : We report on the application of novel small-molecule highly crystalline pentacyclic diamides possessing significant OTFT and OLED potential. Abstract : Developing organic semiconductors for organic thin film transistors (OTFT) and optoelectronic applications is a challenge. We developed highly crystalline pentacyclic diimides (3 ) and (4 ) which showed good OTFT and OLED potential and energy gaps of 2.60 eV and 2.54 eV. They exhibited interesting photo and eletroluminescence activity. Both compounds showed good quantum yields (0.56 for (3 ) and 0.60 for (4 )).